Reformulasi Ketentuan Pengelolaan Data Pribadi sebagai Ius Constituendum dalam Menjamin Perlindungan Data Pribadi Pengguna Layanan Media Sosial - Gio Arjuna Putra (Jurnal Hukum Lex Generalis, 2021)
The high penetration rate of Internet and social media users in Indonesia is inversely proportional to the progressivity of legal and technological development. This can be seen from the unassigned legal product in the state of the Law that explicitly regulates the protection of personal data. Based on the results of studies conducted related to the legal relationship between users and social media service providers, arises through the terms of service as an agreement based on Article 46 paragraph (2) PP No. 71 of 2019. Then the absence of a law that explicitly regulates the rights and obligations of service providers as processors and controllers of personal data raises the issue of legal certainty in guaranteeing the protection of users' personal data.